New records of eight species of ground beetles (Coleoptera, Carabidae) from Colombia (2020)
We report new records of eight species of ground beetles (Coleoptera, Carabidae) from Colombia originated from recent field trips and from museum specimens: Amblygnathus suturalis Putzeys, 1845 (Atlántico), Bembidion chimborazonum Bates, 1891 (Valle del Cauca), Homopterus subcordatus Darlington, 1950 (Caquetá), Hyboptera auxiliadora Erwin, 2004 (Bolívar), Neoaulacoryssus cupripennis (Gory, 1833) (Tolima), Notiobia disparilis Bates, 1878 (Caquetá), Notiobia glabrata Arndt, 1998 (Caquetá), and Trichopselaphus magnificus Ball, 1978 (Valle del Cauca). These records belong to species expected to be found in Colombia, because previous studies have shown their presence in nearby countries, but whose presence in the country was not confirmed so far.